2019
DOI: 10.1186/s13256-019-2147-z
|View full text |Cite
|
Sign up to set email alerts
|

Penile metastases of rectal adenocarcinoma after abdominoperineal resection: a case report

Abstract: Background Penile metastases are very rare and arise most frequently from genitourinary cancers. Penile metastases from rectal adenocarcinoma are less common. Case presentation We report the case of a 47-year-old North Afican man with penile metastases from a rectal adenocarcinoma, which was discovered 4 months after abdominoperineal resection. A penile biopsy was carried out and established the metastatic nature. He underwent palliative chemotherapy treatment. He was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In 40% of patients, priapism is considered a prominent feature. Metastases can present as plaques, wart-like nodules, ulceration, erythema, or induration of the penis ( 5 ). The mass ordinarily progresses to involve the corpora cavernosa with extension into the neighboring perineal subcutaneous tissue, the corpus spongiosum, and bulb ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 40% of patients, priapism is considered a prominent feature. Metastases can present as plaques, wart-like nodules, ulceration, erythema, or induration of the penis ( 5 ). The mass ordinarily progresses to involve the corpora cavernosa with extension into the neighboring perineal subcutaneous tissue, the corpus spongiosum, and bulb ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Boubacar Efared et al disclosed a patient with penile metastasis from rectal adenocarcinoma who accepted his adjuvant chemotherapy (XELOX regimen, oxaliplatin plus capecitabine) ( 4 ). A patient underwent palliative chemotherapy treatment and still alive 4 months after diagnosis of penile metastases ( 5 ). Lee et al reported a patient with metastatic carcinoma from the rectal cancer and the patient was still alive after receiving palliative chemotherapy with modified FOLFOX-6 (mFOLFOX-6; oxaliplatin with 5-fluorouracil and folinic acid) plus bevacizumab ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only 6 cases of penile metastasis in the rectal cancer after neoadjuvant CRT have been reported. [ 3 – 9 ] Among these, 1 patient did not undergo surgery due to exacerbate multiple pulmonary metastasis and 1 patient received only short-course radiotherapy. Pathologic stages II and III were found in 3 patients each.…”
Section: Discussionmentioning
confidence: 99%
“…. 4 Magnetic resonance imaging is the best non-invasive modality for the investigation of penile lesions and helps in assessment of tumor extent and involvement of the neighboring anatomic structures while USG and CT-scan can be helpful in diagnosis. Biopsy is required to differentiate metastasis form primary tumor.…”
Section: Discussionmentioning
confidence: 99%